A Low-Complexity and High-Throughput RTL Design of a BCH (15,7) Decoder - Hendra Setiawan (Journal of ICT Research and Applications, 2012)
The  Bose,  Chaudhuri  and  Hocquenghem  (BCH)  codes  form  a  large class  of  powerful  random-error  correcting  cyclic  codes.  However,  the implementation  of  its  decoder  requires  high-complexity  computation  resources with a huge number of sequential circuits. This paper presents a  low-complexity register transfer level (RTL) circuit design of a BCH decoder. In accordance with the  table  relationship  between  the  syndrome  and  the  error  bit  position,  we propose  a  circuit that  is  mostly occupied by combinational elements without any sequential evolvement. Therefore the designed  system has a  low complexity and high  throughput  properties.  The  implementation  of  the  BCH  (15,7)decoder  on Virtex  5  FX70TFF1136  requires  77  look-up  tables  (LUTs)  with  the  maximum throughput reaching 1.7 Gbps.